Inorganic nanomaterials for intelligent photothermal antibacterial applications - Wang, Bao; Xu, Yan; Shao, Donghan; Li, Leijiao; Ma, Yuqin; Li, Yunhui; Zhu, Jianwei; Shi, Xincui; Li, Wenliang (Frontiers in Bioengineering and Biotechnology, 2022)
Antibiotics are currently the main therapeutic agent for bacterial infections, but they have led to bacterial resistance, which has become a worldwide problem that needs to be addressed. The emergence of inorganic nanomaterials provides a new opportunity for the prevention and treatment of bacterial infection. With the continuous development of nanoscience, more and more inorganic nanomaterials have been used to treat bacterial infections. However, single inorganic nanoparticles (NPs) are often faced with problems such as large dosage, strong toxic and side effects, poor therapeutic effect and so on, so the combination of inorganic nano-materials and photothermal therapy (PTT) has become a promising treatment. PTT effectively avoids the problem of bacterial drug resistance, and can also reduce the dosage of inorganic nanomaterials to a certain extent, greatly improving the antibacterial effect. In this paper, several classical metal-based, metal-like and carbon-based nanomaterials which can be used in PTT are reviewed, and their advantages are discussed and summarized. In addition, we also analyze the future development trend of the remaining problems. We hope that these discussions will be helpful to the future research of near-infrared (NIR) photothermal conversion inorganic nanomaterials.